Defense Economics in Indonesian Macroeconomy: Strategy Defense Industry Independence - Mulyadi, Mulyadi; Nirdukita Ratnawati (Yayasan Riset dan Pengembangan Intelektual, 2024)
Strategies to strengthen the independence of the defense industry must consider various factors, including technological advancements, market demands, and potential collaborations between the public and private sectors. In the context of globalization, Indonesia's defense industry must compete with more advanced products from other countries. The aim of this research is to examine the strategies for achieving defense industry independence within Indonesia's macroeconomic development framework. The findings highlight essential steps and strategies necessary to strengthen Indonesia's defense industry, contributing to national independence and security. With commitment from all stakeholders, the defense industry can evolve and provide substantial benefits to Indonesia’s overall economy.